2012
DOI: 10.3889/mjms.1857-5773.2011.0210
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Symptoms, Immunological Changes, Ventilatory Capacity, and Bronchial Responsiveness in Welders

Abstract: Objective: To evaluate the effect of workplace exposure and its duration on respiratory symptoms, atopic status, ventilatory capacity, and bronchial responsiveness in welders. Material and Methods:We performed a cross-sectional study including 39 males working as stainless steel welders and an equal number of male office workers matched by age, duration of employment and smoking status. Respiratory symptoms and detailed smoking history were recorded by questionnaire. Evaluation of examined subjects included sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…These findings coincide with the findings by Isah [13]. Studies done by Sharifian [29], Stoleski [30], Jani [28] and by Erhabor [31] also showed that with increase duration of exposure (years), symptoms were likely to increase showing an association. In another study in India both morbidities were found to be significantly associated with years of employment among welders than non -welders [32].…”
Section: Discussionsupporting
confidence: 90%
“…These findings coincide with the findings by Isah [13]. Studies done by Sharifian [29], Stoleski [30], Jani [28] and by Erhabor [31] also showed that with increase duration of exposure (years), symptoms were likely to increase showing an association. In another study in India both morbidities were found to be significantly associated with years of employment among welders than non -welders [32].…”
Section: Discussionsupporting
confidence: 90%